Terpaan Tweet Tentang Kpop Idol Mengenakan Scarf Elzatta Hijab Dan Minat Beli (representamen, 2023)
Twitter is a social media platform that can be used to share information and interact with other users. One Twitter account that has received a lot of attention, especially from kpop fans, is @_sunminoflower_. This account does not disclose the owner's personal information (it is anonymous) and is a trending topic because one of the account's most popular tweets, featuring the Elzatta Hijab logo in a photo spread throughout the account. The purpose of this study is to see whether the social media tweet exposure variable @_sunminoflower_ has an impact on buying interest of Elzatta Hijab. This study uses the theory of SOR (Stimulus, Organism, Response). By using a quantitative approach based on the positivism paradigm used for research on certain samples or populations, this research is explanatory in nature. Purposive sampling technique was used to collect a sample of 195 of 380 @_sunminoflower_ followers. Data collection techniques using a questionnaire. The findings of this research analysis can be used to draw conclusions that Elzatta Hijab's purchase intention is significantly influenced by media exposure to the Twitter account @_sunminoflower_. The results of the T test which showed that the research hypothesis was accepted was 8.340 > 1.972. Keywords: Media exposure, Kpop idol, twitter, theory of SOR